KEANEKARAGAMAN MAKROZOOBENTHOS SEBAGAI BIOINDIKATOR KUALITAS PERAIRAN ESTUARI PERCUT SEI TUAN KABUPATEN DELI SERDANG Makrozoobenthos Diversity as Bioindicators of Water Quality of the Estuary Percut Sei Tuan District Deli Serdang - Cut Hannelida Eriza; Yunasfi Djayus; Rusdi Leidonald (AQUACOASTMARINE, 2017)
Percut Sei Tuan Estuary has 3,820 meters length, is influenced by the tide and the shipping line and tourist activity. Macrozoobenthos diversity and the measurement of physical and chemical factors is one of the parameters used to determine changes in water quality in the estuary Percut Sei Tuan. The purpose of this study was to determine the physical and chemical waters in relation to water quality standards under PP No. 82 of 2001 with Storet method as well as the density and macrozoobenthos diversity. This research was conducted over two months, from March until April 2016 Percut Sei Tuan estuary District of Deli Serdang North Sumatera province. Percut Sei Tuan Estuary is categorized at third class water classificatized that can be used for water recreation facilities, fishing ponds and water tourism and for irrigation. Pollution level belongs to the class C is lightly polluted accordance with Method Storet. Values Index Diversity (H') macrozoobenthos obtained at each research station : station 1 is 1,375, station 2 is 1,444 station 3 is 2,050. These results indicate that the diversity of macrozoobenthos was moderate. Pearson correlation analysis results showed that the temperature, salinity and pH highly correlated, BOD5 classified as moderate, and light penetration is low DO and COD relatively very low correlated.Keywords: Estuaries Percut Sei Tuan, Macrozoobenthos Biodiversity, Water Quality